Stress factors in veterinary medicine—a cross-sectional study among veterinary students and practicing vets in Austria - Neubauer, Viktoria; Gächter, Afsaneh; Probst, Thomas; Brühl, Deianira; Dale, Rachel; Pieh, Christoph; Humer, Elke (Frontiers in Veterinary Science, 2024)
Background: Although the issue of high mental health burden among veterinarians is welldocumented in previous studies, little is known about the specific occupational stress factors associated with mental health issues. Therefore, the aims of this study were twofold: 1) to assess occupational stress factors within the veterinary profession, with a particular emphasis on comparing the expectations of veterinary students with the experiences of practicing veterinarians, and 2) to link the experienced stress with mental health indicators in veterinarians.Methods: All registered veterinarians and veterinary-medicine students in Austria were invited to participate in an cross-sectional online survey. The data collection took place during the winter of 2022/2023 and included standardized questionnaires on mental well-being (WHO-5), depression (PHQ-9), anxiety (GAD-7), stress (PSS-4), and insomnia (ISI-2). Additionally, participants were asked about various estimated (students) or experienced (vets) occupational stress factors, which were to be rated on a 5-point Likert scale ranging from 'not at all' to 'very strongly'. An open question invited respondents to identify in free text further experienced/anticipated sources of work-related stressors in veterinary practice.Results: A total of 430 students and 440 veterinarians participated in the study. The results of a repeated measures analysis of variance (ANOVA) indicate that the burden of bureaucracy is perceived as less stressful by students than experienced by veterinarians, all other areas are perceived as more stressful by students than by veterinarians. In veterinarians, bureaucracy is experienced as the most burdensome, followed by animal suffering, and communication with animal owners. Further analysis of possible associations between the extent of perceived stressors and indicators of mental health shows that while bureaucracy is the most burdensome, it has the smallest correlation with mental health indicators. On the other hand, financial concerns, which are not ranked among the main stressors, have the strongest correlation with impaired mental health.Conclusions: The results suggest that financial security for veterinarians is crucial to safeguard their mental health. The training of veterinary medicine students and practicing veterinarians in the areas of administration, time management, handling animal suffering, and communication with animal owners might be beneficial in reducing their job-related stressors. * **